Effect of homocysteine on survival of human glial cells - Škovierová, H; Mahmood, S; Blahovcová, E; Hatok, J; Lehotský, J; Murín, R (Physiological research, 2015)
Several neurodegenerative conditions, such as Alzheimer's disease and Parkinson's disease, or vascular dementia and cognitive impairment, are associated with mild hyperhomocysteinemia. Hyperhomocysteinemia is defined as an increase of the homocysteine (Hcy) level beyond 10 microM. Although the adverse effect of Hcy on neurons is well documented, knowledge about the impact of this amino acid on glial cells is missing. Therefore, with the aim to evaluate the neurotoxic properties of Hcy on glial cells, we used a glioblastoma cell line as a study model. The viability of cells was assayed biochemically and cytologically. At a concentration around 50 microM in the culture medium D,L-Hcy induced cell death. It is noteworthy that Hcy induces cell death of human glial cells at concentrations encountered during mild hyperhomocysteinemia. Therefore, we propose that Hcy-induced impairment of neuronal functions along with damage of glial cells may contribute to the etiopathogenesis of neurodegenerative diseases associated with hyperhomocysteinemia.
Keywords: buněčná smrt; Cell Death; Neurons; homocystein; kultivované buňky; Cells, Cultured; nádorové buněčné linie; Dose-Response Relationship, Drug; Neuroglia; vztah mezi dávkou a účinkem léčiva; neuroglie; Humans; Cell Line, Tumor; Homocysteine; neurony; lidé; viabilita buněk; Cell Survival